What level of support is required to enable secondary school teachers to effectively teach first aid? A randomized trial. (21st July 2020) - Ellis, Lucy; Gordon, Ellen; Forsyth, Mark; Ward, Alexander; Oliver, Emily
Abstract : page_236 other In light of the UK government's decision to make first aid education mandatory in schools, this article adds to the body of evidence to inform the implementation of this decision. Our research aimed to explore whether providing extra support to teachers increased their confidence to teach first aid, and whether this support influenced student learning outcomes. Thirty-five teachers were randomly allocated into two experimental groups and one control group. The first experimental group received support through a video medium, the second through an interactive webinar. The control group was provided with no support beyond the learning materials provided to all participants. Our analysis suggests that while providing support for teachers does not positively affect their confidence to teach first aid in the classroom, this increased support does positively affect the first aid knowledge of students.